Islam Kawasan Tuban Bumi Wali: The Spirit of Harmony - Janeko Janeko (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to examine the history, process of Islamization, and the formation of the religious identity of Tuban Regency as the